Validity of interactive media to strengthen understanding concepts in integer class vii - Fitria, Fitria; Sunismi, Sunismi; Fuady, Anies (Universitas Negeri Yogyakarta, 2024)
This research aims to test the validity of interactive media to strengthen the understanding of concepts in integer material for class VII MTs. The method used is qualitative and descriptive. The research instrument used a questionnaire from 3 experts, two practitioners, and 13 class VII students at MTs At-Taawun. The research results show that according to interactive media design experts, it is valid with a percentage of 91.7%, media experts with 81.7%, material experts with 90%, media practicality with 85.4%, and student trials with a rate of 87.7&. Based on the research results, interactive media on integers was declared valid with an average of 88.9%, so interactive media was declared suitable for use. The results of this research can also be used as a reference for research regarding media validity testing. The media that has been created can be used as learning media during the learning process.